Misteri Buah Ara Dalam Retorika Yeremia 24 - Venantius, Supriyono; Ule, Silvester; Kota, Dominggus Mite (Institut Filsafat dan Teknologi Kreatif Ledalero, 2024)
This article aims to present an analysis of Jeremiah 24:1-10, with a focus on the text's structure and rhetoric. This research treats Jeremiah 24:1-10 as a cohesive unit, differing from the views of redactional theorists who commonly consider verse 1b in Jeremiah 24:1-10 as a redactional addition. According to them, reading Jeremiah 24 without verse 1b would not significantly impact the understanding of the passage. Verse 1b, mentioning King Jeconiah, the officials of Judah, the artisans, and the smiths, is added as propaganda reflecting Jeconiah’s claims or legitimization and that of his supporters to live and rule in Jerusalem and Judah. In contrast to this perspective, this article views verse 1b as one of the structural and rhetorical elements that demonstrate how the text is organized. This article will identify structural devices such as keyword repetitions and contrasts that can indicate the rhetoric or persuasive techniques employed in the text. The analysis finds that Jeremiah 24:1-10 contains rhetoric of God's mysterious providence, showcasing God's full authority to change or determine the fate of nations or kingdoms that humans sometimes cannot comprehend. Key words : rhetoric, providence, mystery, paradox, quality, civilisation